Genetic, epigenetic and enviromental influencing factors on the regulation of precocious and delayed puberty - Faienza, Maria Felicia; Urbano, Flavia; Moscogiuri, Luigi Antonio; Chiarito, Mariangela; De Santis, Stefania; Giordano, Paola (Frontiers in Endocrinology, 2022)
The pubertal development onset is controlled by a network of genes that regulate the gonadotropin releasing hormone (GnRH) pulsatile release and the subsequent increase of the circulating levels of pituitary gonadotropins that activate the gonadal function. Although the transition from pre-pubertal condition to puberty occurs physiologically in a delimited age-range, the inception of pubertal development can be anticipated or delayed due to genetic and epigenetic changes or environmental conditions. Most of the genetic and epigenetic alterations concern genes which encode for kisspeptin, GnRH, LH, FSH and their receptor, which represent crucial factors of the hypothalamic-pituitary-gonadal (HPG) axis. Recent data indicate a central role of the epigenome in the regulation of genes in the hypothalamus and pituitary that could mediate the flexibility of pubertal timing. Identification of epigenetically regulated genes, such as Makorin ring finger 3 (MKRN3) and Delta-like 1 homologue (DLK1), respectively responsible for the repression and the activation of pubertal development, provides additional evidence of how epigenetic variations affect pubertal timing. This review aims to investigate genetic, epigenetic, and environmental factors responsible for the regulation of precocious and delayed puberty.